Análisis de asociación genética entre el SNP RS914458 del gen proteína tirosina fosfatasa no receptor tipo 1 (ptpn1) y diabetes tipo 2 en población peruana - Paredes Anaya, Mónica (2014)
Genetic association analysis between snp rs914458 of protein tyrosine phosphatase, non- receptor type 1(ptpn1) gene and Type 2 Diabetes in Peruvian Population